Effects of reduced glutathione supplementation in semen freezing extender on frozen-thawed bull semen and in vitro fertilization - Kazuko OGATA; Akira IMAI; Shinya SATO; Kagetomo NISHINO; Shinya WATANABE; Tamas SOMFAI; Eiji KOBAYASHI; Kumiko TAKEDA (The Society for Reproduction and Development, 2021)
During cryopreservation, spermatozoa may suffer cold and cryo-induced injuries -associated with alterations in cell defense systems- that are detrimental to their function and subsequent fertility. This study aimed to determine the efficacy of supplementing the semen freezing extender with the antioxidant reduced glutathione (GSH) in cattle. Semen was collected from four bulls and diluted in a freezing extender supplemented with or without GSH (0, 1, 5, and 10 mM) before the cooling step of the cryopreservation process. After thawing, the quality of the frozen-thawed semen was investigated for motility, viability, acrosomal and DNA integrity, and subsequent embryo development after in vitro fertilization of bovine oocytes. Additionally, semen from one of the bulls was used to analyze semen antioxidative potential, sperm penetration into oocytes, male pronucleus formation rate, and embryo DNA integrity. The sperm quality varied among bulls after GSH supplementation. One bull had decreased sperm total motility, and two bulls had decreased sperm DNA integrity. GSH supplementation had positive effects on embryo development for three bulls. Two of them showed both improved cleavage and blastocyst formation rates, while the other one only showed an improved cleavage rate. We observed positive effects on early male pronucleus formation and no negative effects on DNA integrity and cell number in blastocyst stage embryos. Although the effect varies depending on individual bulls and GSH concentration, GSH supplementation in semen may improve in vitro embryo production from frozen semen.